Enhancing electromechanical properties of CaBi2Nb2O9 thin films grown on Si. Issue 15 (15th November 2016) - Zhang, Yunxiang; Wang, Chun-Ming; Li, Yao; Cheng, Hongbo; Liu, Menglin; Xue, Caihong; Xu, Huiwen; Ouyang, Jun
Abstract: In this work, ferroelectric CaBi2 Nb2 O9 thin films were grown on Yttria-stabilized zirconia (YSZ)-buffered (100) Si substrate via radio-frequency magnetron sputtering. X-Ray diffraction analysis showed that the CaBi2 Nb2 O9 films were (200/020) textured, while the commonly-observed (00 l ) grains which are weakly polarizable have been eliminated. Enhanced dielectric (~533 @ 5 kHz) and ferroelectric properties ( P r ~ 13μC/cm 2, P s ~55 μC/cm 2 @ 1 kHz) were achieved in this high Tc piezoelectric material, leading to a significant improvement of the d 33 piezoelectric modulus (from ~15–20 pm/V to ~30 pm/v). The method of strain engineering used in this work can be applied to the integration of other bismuth-layer structured ferroelectrics into Si-based microelectronics.